Reseeding Native Species Promotes Community Stability by Improving Species Diversity, Niche, and Interspecific Relationships in the Desert Steppe of Northwest China - Haixin Jiang; Yao Zhou; Wen Li; Qi Lu; Dongmei Xu; Hongbin Ma; Xingzhong Ma; Xiaowu Tian (Ecology and Evolution)
ABSTRACT The mechanism of community stability is a hot topic in the field of ecology. Research on the stability of the grassland community has gradually increased, and the reseeding of native species is one of the main measures to restore the degraded desert steppe in northwest China. However, little is known about the changes in the stability of the plant community in the desert steppe after reseeding native species. This study established a long‐term observation site for native species reseeding in the desert steppe. We established reseeding and grazing exclusion plots in May 2017 and conducted surveys on degraded grasslands (0YEX(RS)) before setting up reseeding and grazing exclusion treatment experimental plots. After 3 and 6 years of setting up the test, the vegetation restoration status of the plot was investigated, respectively. The results showed that reseeding native species increased the Shannon‐Wiener index and Margalef index of the community. At the same time, the importance value and the breadth of the niche of gramineous plants improved, while the proportion of pairs of high niche overlaps and the logarithm of significant association decreased. The general association of reseeding of the desert steppe was positively correlated, and the stability of the community gradually increased. The results of partial least squares path modelling show that reseeding has a highly significant positive effect on community stability. Both the EX (grazing exclusion grassland) and RS (reseeded grassland) models indicate that niche and diversity indices influence community stability to varying degrees, while interspecific linkage coefficients affect mainly niche overlap. Our research has shown that reseeding native species can improve the intensity of competition between species for resources, leading to a more stable community and ultimately increasing species diversity and community stability. These findings provide valuable theoretical support for vegetation restoration and sustainable management in the desert steppe.